Strategi Pendekatan Penal Dan Non Penal Dalam Upaya Perlindungan Guru Di Sekolah - Euis Sopiah (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
In the last few decades, teachers in carrying out their duties have often become the subject of social control and mass media. This is due to the increasing number of acts of violence that occur in schools, both committed by students, parents, school administrators and even teachers themselves. These acts of violence sometimes occur due to student disciplinary activities carried out by teachers. The aim of this research is to provide an explanation of the importance of clear regulations regarding the protection of teachers in carrying out their duties. The research method used is a literature review. The results of this research are that the current regulations are not strong enough to provide legal protection for teachers in carrying out their duties, so there is a need for clearer legal evidence and more emphasis on teachers in carrying out their duties.